2011
DOI: 10.1097/smj.0b013e31821a841d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinical Vignettes on Senior Medical Students' Opinions of Climate Change

Abstract: Our results suggest that student physician attitudes to climate change are mutable. Priming students into "medical mode" may alter their opinions on the scientific merit of nonmedical issues, and may be a vestige of a hidden medical curriculum. Further studies should explore the interrelationship between other sociopolitical beliefs and medical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although it was not the purpose of this study to explore in how far medical school curriculum changes would influence individual FYMS' opinion on tackling global climate change as part of their daily work as a doctor, previous research on the subject confirms our assumption that this connection exists. As early as 2011, an American research group showed in a series of experiments that the opinions of medical students on climate change are mutable [39]. There is thus a great opportunity for the medical profession to educate students about the emerging problem of global climate change, its health effects and their future role in addressing this global threat.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not the purpose of this study to explore in how far medical school curriculum changes would influence individual FYMS' opinion on tackling global climate change as part of their daily work as a doctor, previous research on the subject confirms our assumption that this connection exists. As early as 2011, an American research group showed in a series of experiments that the opinions of medical students on climate change are mutable [39]. There is thus a great opportunity for the medical profession to educate students about the emerging problem of global climate change, its health effects and their future role in addressing this global threat.…”
Section: Discussionmentioning
confidence: 99%
“…The nurses pointed out that their daily work was centered around the individual patient and was restricted by time and budget constraints, which were more urgently felt than climate change. Moreover, Prasad et al investigated senior medical students’ perception on climate change and revealed that the urgency to act on climate change was lower in a group primed with a medical case study, suggesting that being in a “medical mode” lowered medical student’s sense of urgency for climate change [ 72 ]. These findings by Anaker and Prasad show that the topic of climate change has a rather low priority in the medical setting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research on medical students'; attitudes towards climate change revealed that these attitudes are mutable and coloured by how the attitudes appear with respect to medical opinion on climate change (Prasad et al . ).…”
Section: Discussionmentioning
confidence: 99%